Penerapan Metode Diskusi dalam Peningkatan Minat Belajar - Irwan Irwan (Institut Agama Islam Negeri Palopo, 2018)
This research is a classroom action research (CAR) which aims to determine the increasing interest in learning through discussion methods. Subjects in the study were students of class X-7 as many as 24 students (11 sons and 13 daughters) SMA 4 Kota Palopo. The results showed that: the application of the discussion method was carried out in 3 stages: a). The stage before a meeting. b). The stage during the meeting and c) Stage after the meeting. Then before the researcher conducts research in class. Researchers first take student data to the teacher in the field of Islamic Education as a comparison of the results of pre-cycle learning, the cycle I and cycle II. The average value of students in class X-7 before applying the discussion method is only 47.08%, which means that it is still below the limit of students' completeness. In the first cycle, researchers have applied the discussion method to the average value of students reaching 69.5%. In cycle II the average value of students reached 84.16%. This has proven that the application of the discussion method can improve students' learning interest in the subjects of Islamic Religion in the X-7 class of SMA 4 Palopo.